Effect of Coconut Milk Supplementation to Nutritional Status Parameters in Liver Cirrhosis Patients - Suwito Indra; Rino Alvani Gani; Ari Fahrial Syam; Hamzah Shatri (The Indonesian Society for Digestive Endoscopy, 2015)
Background: Liver cirrhosis is on of health problems in Indonesia. Decreasing number of liver cells in cirrhosis cause some complications, one of which is malnutrition. In Indonesia, coconut milk is one of nutrients sources which quite popular. Coconut milk is thought to have hepatoprotective effect and be able to be eliminated by cirrhosis patients. A study about effect of coconut milk supplementation to nutritional status parameters in liver cirrhosis patients is really needed.Method: This study is a randomized controlled trial with parallel design. This study is conducted in Cipto Mangunkusumo Hospital Jakarta from February to March 2014. Patients are given late night snack (LNS) in form of agar that contained 25 grams of sugar and additional 50 cc coconut milk in group I (experimental group) and additional drink that contained 25 grams of sugar in group II (control group). Variables that measured to look changes in nutritional status between the two groups are triceps skinfold thickness (TSF), mid arm muscle circumference (MAMC), body mass index (BMI), body fat mass (BFM), prealbumin levels and serum albumin levels.Results: A total of 35 patients with liver cirrhosis in this study to the completion. There are three parameters of nutritional status that increasing better in the group receiving a LNS from combination of carbohydrates and coconut milk, compared to group receiving carbohydrates alone. Those three parameters are mean (SD) MAMC with amount of 9.41 (6.43) mm in group I and 4.68 (5.76) mm in group II, p = 0.028. Median (range) BFM changes 0.67 (-2.47-3.80) kg in group I and 0.21 (-4.96-1.99) kg in group II, p=0,373. Mean (SD) serum albumin level change 0.17 (0.31) g/dL in group I and 0.07 (0.41) g/dL in group II, p = 0,426. There is an increase in the TSF measurement in all subjects after one month of LNS supplementation, but not found any significant differences of TSF changes between the two groups. While the measurement of BMI and serum prealbumin did not show any significant changes after treatment in all subjects research.Conclusion: One month LNS 200 kkal supplementation with combination of carbohydrates and coconut milk have a better effect on the improvement of nutritional status in patients with liver cirrhosis, compared to carbohydrates alone. This shown by the better parameters of MAMC, BFM and increased serum albumin in group I, compared to group II.